Exploiting an Elitist Barnacles Mating Optimizer implementation for substitution box optimization - Kamal Zuhairi, Zamli; Din, Fakhrud; Alhadawi, Hussam S.; Khalid, Shah; Alsolai, Hadeel; Nour, Mohamed K.; Al-Wesabi, Fahd N.; Assam, Muhammad (Korean Institute of Communications and Information Sciences, 2023)
Barnacles Mating Optimizer (BMO) is a new metaheuristic algorithm that suffers from slow convergence and poor efficiency due to its limited capability in exploiting the search space and exploring new promising regions. Addressing these shortcomings, this paper introduces Elitist Barnacles Mating Optimizer (eBMO). Unlike BMO, eBMO exploits the elite exponential probability (Pelite) to decide whether to intensify search process via swap operator or to diversify search by randomly exploring new regions. Furthermore, eBMO uses Chebyshev map instead of random numbers to generate quality S-boxes. Experimental results of eBMO on the generation of 8 × 8 substitution-box are competitive against other existing works.